Pheochromocytoma-Induced Inverted Takotsubo-Like Cardiomyopathy Leading to Cardiogenic Shock Successfully Treated With Extracorporeal Membrane Oxygenation. (September 2015) - Flam, Benjamin; Broomé, Michael; Frenckner, Björn; Bränström, Robert; Bell, Max
Pheochromocytoma classically displays a variety of rather benign symptoms, such as headache, palpitations, and sweating, although severe cardiac manifestations have been described. We report a case of pheochromocytoma-induced inverted takotsubo-like cardiomyopathy leading to shock and cardiac arrest successfully treated with extracorporeal membrane oxygenation (ECMO) as a bridge to pharmacological therapy and curative adrenalectomy. A previously healthy 46-year-old woman presented to the emergency department with abdominal pain, dyspnea, nausea, and vomiting. Clinical evaluation revealed cardiorespiratory failure with hypoxia and severe metabolic acidosis. Computed tomography (CT) scan showed pulmonary edema and a left adrenal mass. Transthoracic echocardiography (TTE) displayed severe left ventricular dysfunction with inverted takotsubo contractile pattern. Despite mechanical ventilation and inotropic and vasopressor support, asystolic cardiac arrest ensued. The patient was resuscitated using manual chest compressions followed by venoarterial ECMO. Repeated TTEs demonstrated resolution of the cardiomyopathy within a few days. Laboratory results indicated transient renal and hepatic dysfunction, and CT scan of the brain displayed occipital infarctions. Biochemical testing and radionuclide scintigraphy confirmed a pheochromocytoma. Pharmacological adrenergic blockade was instituted prior to delayed adrenalectomy after which the diagnosis was histopathologically verified. The patient recovered after rehabilitation. We conclude that pheochromocytoma should be considered in patients presenting with unexplained cardiovascular compromise, especially if they display (inverted) takotsubo contractile pattern. Timely, adequate management might involve ECMO as a bridge to pharmacological therapy and curative surgery.